Memes como estratégia de comunicação organizacional: relacionamento e produção de sentidos de universidades federais brasileiras no Facebook - Neves, Luiz Felipe Fernandes (2019)
The popularization of the internet and the social media has accompanied the constant creation and circulation of so-called memes: messages in text and/or image, generally humorous and made up of coarse and amateur montages, which undergo repeated reappropriations, modifications and resignifications as they are being shared. The mere fact of attracting the attention of a vast and varied audience was enough for the internet meme becoming appropriated for marketing, institutional, political, and other purposes, at a time when the word engagement seems to dominate the actions of the professionals of Communication. In this sense, and focusing on Brazilian federal universities, this work investigated the appropriation that these institutions have made of this type of strategy to achieve their goals in terms of organizational communication in Facebook, especially those related to the relationship with stakeholders and the production of meanings. To support the research, the theoretical framework was divided into two axes: the meme as a communication phenomenon, in which concepts such as cyberculture and cyberspace, mediatization, social media, virtual communities, collective intelligence and humor are worked on; and the organizational communication in a digital environment, with the presentation of the studies related to the communication processes in the organizations, their strategic dimension and the commitment of the universities with the public communication. For the analysis was selected a sample of 46 memes produced by 24 Brazilian federal universities, in addition to questionnaires answered by producers of five of these institutions. The results show how the process of mediatization conforms the senses of the memes, contributing to the approximation of the institutions with their publics. They also reveal that humor plays a fundamental role in the interactivity and engagement generated by this type of message, and can act decisively in the construction of the institutional image and public communication.